Magical passes the practical wisdom of the shamans of ancient Mexico - Castaneda, Carlos 1931-1998 (New York, NY HarperCollinsPublishers, 1998)
"Thirty years ago, Carlos Castaneda published The Teachings of Don Juan, the story of a magical journey into the unknown. Under the tutelage of don Juan Matus, the young anthropologist entered another world and emerged to give readers of his first book glimpses of the "nonordinary reality" of a Yaqui Indian sorcerer. Castaneda wrote eight more books, most recently The Art of Dreaming, which describes don Juan's teaching methods as well as the sorcery arts he made Castaneda practice." "Castaneda learned that for us to perceive any of the worlds that exist beside our own, we must not only covet them but find sufficient energy to seize them. Magical Passes offers readers the key to this energetic conditioning for the first time. In his revolutionary new book, Castaneda reveals a series of body positions and physical movements that have enabled various shamans and their apprentices to navigate their own sorceric journeys." "The magical passes described in this unusual new volume allow those who practice them to travel the same road as the Mexican sorcerers and their apprentices - in addition to Carlos Castaneda, the apprentices of don Juan include Florinda Donner-Grau, Taisha Abelar, and Carol Tiggs - and to honor don Juan's quest while embarking on their own exploration into unknown worlds. The movements described in Magical Passes allow the practitioner to achieve new levels of physical and mental vitality."--Jacket.
Magical passes -- Tensegrity -- Six series of tensegrity -- The first series : the series for preparing intent -- The second series : the series for the womb -- The third series : the series of the five concerns : the westwood series -- The fourth series : the separation of the left body and the right body : the heat series -- The fifth series : the masculinity series -- The sixth series : devices used in conjunction with specific magical passes.
Keywords: Juan -- Don -- 1891-1973.; Castaneda, Carlos -- 1931-1998.; Shamanism -- Mexico; Exercise -- Religious aspects; Indians of Mexico -- Religion; Mexico -- Religion